2021
DOI: 10.3390/ijerph181910427
|View full text |Cite
|
Sign up to set email alerts
|

A Realist Inquiry to Identify the Contribution of Lean Six Sigma to Person-Centred Care and Cultures

Abstract: A lack of fidelity to Lean Six Sigma’s (LSS) philosophical roots can create division between person-centred approaches to transforming care experiences and services, and system wide quality improvement methods focused solely on efficiency and clinical outcomes. There is little research into, and a poor understanding of, the mechanisms and processes through which LSS education influences healthcare staffs’ person-centred practice. This realist inquiry asks ‘whether, to what extent and in what ways, LSS in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(82 citation statements)
references
References 106 publications
(218 reference statements)
0
54
0
Order By: Relevance
“…However, LSS as a process improvement methodology has a focus on developing the capabilities of teams (doctors, nurses, and administrative and support staff) to manage and continuously improve their work [ 61 ]. As a learning organization, the study site also recognizes that when an organization begins to adopt LSS, individual and team-based learning is the focus, not just in the classroom, but in the practice area [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, LSS as a process improvement methodology has a focus on developing the capabilities of teams (doctors, nurses, and administrative and support staff) to manage and continuously improve their work [ 61 ]. As a learning organization, the study site also recognizes that when an organization begins to adopt LSS, individual and team-based learning is the focus, not just in the classroom, but in the practice area [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the approach to the use of LSS within the study site was synergistic with the concepts of respect for persons and staff empowerment, themselves enablers of person-centered cultures [ 61 ]. The development of staff through support and respect is important for their engagement with LSS [ 2 , 3 ], and staff involved in this project advised they felt respected. We also experienced that the approach of giving to employees opportunities for development through the LSS education and training program within the hospital, rather than getting something from them, such as more productivity [ 63 ] is also synergistic with the person-centered value of respect for persons, which is enabled by empowering cultures [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CTQ is designed to capture the key measurable characteristics of a process or service whose performance standards must be met to satisfy the service user [34] VOC Voice of the Customer Engaging with the customer to gather their feedback about their experiences with and expectations for your products or services [1,2,35] Gemba Observation of the actual process taking place [36] Fishbone Identifies root causes, representing the effect and the factors or causes influencing it [32] 5S…”
Section: Methodsmentioning
confidence: 99%